Symbolic Language in the Rimpu Tradition of the Bima Community as a Medium of Islamic Value Education: An Analysis of Religiosity, Modesty, and Cultural Identity - Ma'ruf Jamaluddin; Baharuddin Baharuddin; Rabiyatul Adawiyah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study examines the symbolic language embedded in the Rimpu tradition of the Bima community as a medium for Islamic value education through the representation of religious values, modesty, and cultural identity. The study focuses on the symbolic forms of Rimpu, the social meanings contained in Rimpu Mpida and Rimpu Colo, and the function of Rimpu in shaping the identity of Mbojo women and instilling Islamic values based on local wisdom. This research employed a qualitative approach using the ethnography of communication. Data were collected through observation, in-depth interviews, documentation, and the recording of cultural terms, particularly Rimpu Mpida, Rimpu Colo, Tembe Nggoli, Maja Labo Dahu, and Nggahi Rawi Pahu. The findings reveal that Rimpu functions as a nonverbal sign system that conveys messages of religious obedience, aurat protection, self-honour, women’s social status, modesty, and moral responsibility in public spaces. Rimpu Mpida marks unmarried women through a more closed form of body covering, whereas Rimpu Colo identifies married women through a style of wearing that leaves the face more visible. Tembe Nggoli strengthens the meaning of Rimpu as a material cultural heritage of Bima because it is closely related to weaving traditions, simplicity, local skills, and appreciation of women’s work. The philosophy of Maja Labo Dahu provides a moral foundation for wearing Rimpu because it teaches shame and fear of violating religious and customary norms. As a medium for Islamic value education, Rimpu instills proper dress ethics, awareness of covering the aurat, social modesty, self-control, respect for women, and local Islamic identity through family habituation, community role models, cultural festivals, and local education. Amid social change, Rimpu has shifted from everyday attire to a cultural symbol in parades, traditional events, schools, and ceremonial spaces. This shift does not erase the meaning of Rimpu but changes the space of its use; therefore, it needs to be strengthened through value education so that younger generations recognize Rimpu not merely as traditional clothing, but also as a bearer of religious, moral, and cultural identity messages. This study contributes to ethnolinguistic, anthropolinguistic, and local wisdom-based Islamic education studies by positioning Rimpu as cultural language, clothing symbolism, social practice, and a medium for transmitting Islamic values within the Bima community.